Not all conservation “policy” is created equally: When does a policy give rise to legally binding obligations? - Justine Bell‐James; Rose Foster; Miguel Frohlich; Carla Archibald; Claudia Benham; Megan Evans; Pedro Fidelman; Tiffany Morrison; Liza Rolim Baggio; Peter Billings; Nicole Shumway (Conservation Letters)
Abstract In many countries, complex environmental problems such as biodiversity decline are regulated at the national level by a disparate range of laws and nonstatutory policy instruments variously described by terms including plans, strategies, guidelines, statements of intent, and/or incentives. Such instruments are often grouped together by conservation policymakers and scientists under the umbrella term “policy.” However, from a legal perspective, there are critical differences between these so‐called policy instruments. In this paper, we focus on what we consider to be the critical difference: whether a policy instrument is binding, and therefore whether an administrative decision (e.g., about a development proposal) can be legally challenged due to noncompliance with that policy instrument. Drawing from international examples, the aim of this paper is to give conservation policymakers and scientists the guidance needed to critically differentiate between laws and nonstatutory policy, assess current or proposed policies, and determine whether a nonstatutory instrument gives rise to binding obligations, thus allowing for decisions to be challenged before a court. In doing so, we encourage conservation scientists, policymakers, activists, and practitioners to reflect critically on what is possible and not possible when nonstatutory “policy” instruments are designed and implemented.